Celebrity Worship Dan Materialism Serta Pengaruhnya Terhadap Compulsive Buying Merchandise Pada Generasi Milenial Di Purwakarta - Ade Nurhayati Kusumadewi; Ropi Marlina; Amna Mawardi; Azizah Tu’sadiyah (Eqien - Jurnal Ekonomi dan Bisnis, 2023)
This study aims to determine the effect of Celebrity Worship and Materialism on Compulsive Buying Merchandise in the Millennial Generation in Purwakarta. The research method used is descriptive quantitative. The population of this study is the Millennial Generation in Purwakarta whose number is known by using a sampling technique, namely incidental sampling of 100 respondents. Methods of data collection using a questionnaire. The data analysis method used is instrument test, classic assumption test and hypothesis testing using SPSS version 25. The results of this study indicate that partially Celebrity Worship has a positive and significant effect on Compulsive Buying Merchandise in the Millennial Generation in Purwakarta, Materialism has a positive and significant effect on Compulsive Buying Merchandise in the Millennial Generation in Purwakarta. and simultaneously celebrity worship and materialism have a positive and significant effect on Compulsive Buying Merchandise in the Millennial Generation in Purwakarta Keywords: Celebrity Worship, Materialism, Compulsive Buying